GROUP GUIDANCE SERVICES MANAGEMENT OF BEHAVIORAL TECHNIC HOMEWORK MODEL - A M., Juhri (Universitas Muhammadiyah Metro, 2013)
Abstract: This simple paper describes the implementation of management guidance service groups using the model home visits behavioral techniques (behavior technic homework). The ideas outlined in this paper are intended to add insight for counselors in the management of the implementation of counseling services group that carried out effectively. This simple paper is expected to be used as reference studies in theoretical matters relating to the management guidance services group, for counselors to students both need guidance services and those who passively as they face various problems difficulties martial jar and obstacles in the achievement of learning ,In general, this study aims to provide insight in particular in the development of social skills for students, especially the ability to communicate with the participants of the service (students) more While specifically to encourage the development of feelings, thoughts, perceptions, insights and attitudes that support embodiments behavior Iebih creative and effective in improving communication skills both verbal and non-verbal for students.Keyword: counselor, counseling, group, student